Tren Fashion Syariah dalam Digitalisasi Marketing di Era Milineal dan Gen Z - Sudarmi; Awaluddin, Murtiadi; Syam, Agus; Mahmuddin (Economic Reviews Journal, 2024)
In the current era of digitalization of marketing, fashion is developing very rapidly, including Muslim or sharia fashion, so with this development, the author wants to know what fashion trends among millennial and generation Z children are in accordance with sharia rules and wants to know the understanding of millennial and gen Z children regarding ethical behavior. get dressed. The method used is a literature review using a descriptive qualitative approach, by reviewing several literature articles, then concluding the results of the problem, namely that the millennial generation and Gen Z with digital marketing are increasingly fashionable due to the ease of accessing various fashion models and in fashion they only consider it as covering the body (aurat), increasing self-confidence and self-identity as a Muslim, but does not pay attention to or understand the rules and ethics in applying fashion trends.